Prevalence Of Goiter and The Status of Iodized Salt Among the Primary School Children of a Rural District in Central India - Shinde, Mohan; Joshi, Ankur; Naik, Govind; Trivedi, Anshuli (National Journal of Community Medicine, 2015)
Introduction: Iodine deficiency disorders are one of the most common public health problems throughout India. The long term goal of salt iodization is elimination of iodine deficiency and re- duction of goiter rate in school aged children. Objective of the study was to find out the prevalence of goiter in primary school children. Methods: In a cross sectional study, a total of forty-seven villages (about 5%) having primary schools, were selected by systematic random sampling method to study the prevalence of goiter and the status of iodized salt at consumer and distribution level. Results: The overall prevalence of goiter in the primary schools children is estimated about 21.23%. Thus it falls under moderate IDD. In the study maximum 311 (53.25%) salt samples have shown 15 ppm iodine. Conclusion: Goiter prevalence is still a public health problem in study area even after the introduction of iodized salt.